Sixth contribution to the study of the Lithosiini of Gabon: the genus Pseudopoliosia Krüger, 2015 (Lepidoptera: Erebidae: Arctiinae) - Durante, Antonio; Apinda-Legnouo, Emelie Arlette (Zootaxa, 2022)
The genus Pseudopoliosia Krüger, 2015 is recorded for the first time in Gabon. Two new species are described, and a checklist and keys to the species are provided.